Innovation and development of a high pressure water nozzle discharged with curtain spray for oil leakage in offshore - Muhammad Nadzir, Nordin (2013)
This study deals with the development of high pressurized water nozzle using dispersion method for oil leakage in offshore. The objectives of this project are to design a new spray nozzle using theoretical data and comparison with already existed nozzle, AFEDO nozzle. The nozzle is design with 5 degree reduction and 3 discharged holes of 0.5 cm in diameter. Computational study of the flow was done by using ANSYS CFX to study the distribution of the flow. Experiment was done at PIMMAG PD Base in Port Dickson, Negeri Sembilan with pressure of 80 psi / 5.5 bar. Results obtain from both analyses show a significant spray pattern and flow distribution as well as distance